The Epistemology of Tajweed in the Book Ar-Ri'ayah by Imam Makki - Alwi Salam; Rohanda Rohanda; Sulthan Zainul Amin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to analyze the epistemology of tajwid science in the book Al-Ri'ayah of Imam Makki bin Abi Talib, including sources of knowledge, construction methodology, and validation criteria for tajwid rules. Using a descriptive qualitative literature research method, this study analyzes the primary texts of Al-Ri'ayah and supporting literature through textual-conceptual analysis with a philosophical-historical approach. The results show that Imam Makki built the epistemology of tajwid on four integrated sources of knowledge: authentic narration with clear sanad, empirical observation of speech organs and acoustic phenomena, rational analysis to reveal logical principles, and ijmaʾ of the imams of qiraʾah. The methodology of the presentation combines precise definitions, descriptions of practices, philosophical analysis, concrete examples from the Qur'an, and recognition of legitimate variations between reading traditions. The validation of the rules uses three objective criteria: internal coherence, correspondence to phonetic reality, and pragmatism in producing clear and sunnah-compliant readings. The epistemology of the Makki Imam demonstrates a model for integrating diverse sources within a coherent framework that can serve as a methodological reference for contemporary Islamic scholarship and can restore the philosophical dimension of tajwid lost in modern understanding.